2013
DOI: 10.4081/ijas.2013.e27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Vitamin C and Soybean Lecithin in the Nutrition of Brown Bullhead (Ameiurus NebulosusL.) Fingerlings

Abstract: The effects of different forms of vitamin C and soybean lecithin on growth performance, feed utilization and body composition of brown bullhead (Ameiurus nebulosus, Lesuer 1819) were evaluated during a 9-week growth trial. A special interest was to investigate a possible combine effect of these nutritional components. The diets used contained three forms of vitamin C (crystallized ascorbic acid, encapsulated L-ascorbic acid and Ca-L-threonate) (100 mg/kg) with and without the combination of soybean lecithin. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Diet change from FM to SBM and BY presents several metabolic and health challenges for farmed fish. When compared to the results of growth of brown bullhead promoted by vitamin C and soybean lecithin 7 , the feed conversion rate of fish in the present study was more effective. The average SGRw values were somewhat lower, compared to the 7 , which can be explained by the older fish category and the less pronounced metabolic rate of the analysed fish in the present study 26 .…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Diet change from FM to SBM and BY presents several metabolic and health challenges for farmed fish. When compared to the results of growth of brown bullhead promoted by vitamin C and soybean lecithin 7 , the feed conversion rate of fish in the present study was more effective. The average SGRw values were somewhat lower, compared to the 7 , which can be explained by the older fish category and the less pronounced metabolic rate of the analysed fish in the present study 26 .…”
Section: Discussionmentioning
confidence: 46%
“…conducted a the long-term feeding trial (6 months) of rainbow trout (Onchorinchus mykiss) with the complete replacement of FM with a combination of vegetable protein and confirmed the significant difference in weight gain only after 12 weeks, thereby highlighting the importance of longer-term feeding studies. Duration of the present feeding study is considered adequate for the investigated species compared to similar research 7,56 . Growth performance retardation was detected in the fish fed 75% and 100% of FM substitution, irrespective of the inclusion of BY.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, El-Sayed et al [ 21 ] stated that Nile tilapia treated with SBL showed increased carcass protein and lipid contents. High protein content can be related to the role of lecithin, rich in phospholipids, in reducing the energy needed for the biosynthesis of phospholipids [ 54 ]. In addition, increased lipid content results from the depletion of digested and absorbed lipids from the intestines due to SBL feeding [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lecithin considers an important source of bioavailable phospholipids (PL) to aquatic animals, with a significant role in energy production through nutrients metabolism, and as an essential component of biological membranes in all eukaryotic cells (Aničić et al, 2013).…”
mentioning
confidence: 99%